Efektivitas Tugas Camat dalam Melakukan Fasilitas Penyusunan Peraturan Desa dan Peraturan Kepala Desa - Sukma, Rooslia; Salmon, Hendrik; Bakarbessy, Andress Deny (TATOHI: Jurnal Ilmu Hukum, 2021)
Introduction: One of the tasks of the sub-district head is to facilitate the preparation of the Perdes, but in practice many villages in Ambon City do not yet have a Perdes. The legal issue is whether the camat is effective in facilitating the preparation of village regulations in Ambon City. Purposes of the Research: The purpose of this study was to determine and analyze the effectiveness of the camat's duties in facilitating the preparation of village regulations and village head regulations.Methods of the Research: The type of research used is sociological juridical, namely a research in the field of law that aims to examine the implementation of legislation, legal principles, legal rules in society, the data of this research are primary data and secondary data.Results of the Research: The results showed that the Camat was not effective in the task of facilitating the preparation of village regulations because of the absence of communication, coordination between the sub-district and village government and efforts to foster in the preparation of village regulations. This is influenced by weak supervision of the sub-district head and the absence of sanctions for the sub-district head to be ineffective in carrying out his duties, as well as the lack of compliance with applicable laws.